Finite elements with boundary interpolation applied to the solid mechanics field problem - De Langhe, K. (Computers & structures, 1995)
In the following paper, a modified interpolation scheme for finite elements is presented. This interpolation is postulated on the boundary of an element only and generates more accurate elements with respect to stiffness matrix and nodal force vector. The technique is discussed for the 2-D linear elastostatic case. Some relevant examples are presented to demonstrate the efficiency of the method.